Pendidikan Kristen Berbasis Kearifan Lokal Masyarakat Adat Suku Moi: Studi Deskriptif-Analitis - Aris Kusmiran Winandar; Simon Aponno; Rini Fonataba; Maria Rumangesan (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2026)
This study aims to examine the implementation of Christian education based on local wisdom in the indigenous people of the Moi Tribe in Southwest Papua, as well as analyze its contribution to the formation of character, cultural identity, and spirituality of the community. The approach used in this study is qualitative with a descriptive-analytical type. The results of the study show that the indigenous people of the Moi Tribe have a strong local wisdom system, one of which is through the Kambik traditional education system which functions as a medium of transmission of cultural values for generations. This system contains values such as leadership, social solidarity, respect for nature, and awareness of cultural identity. The findings of the study also show that there is an alignment between the values of local wisdom and the teachings of the Christian faith, thus allowing integration through an inculturative approach. However, the implementation of education based on local wisdom still faces challenges, such as the dominance of a formal curriculum that is less contextual, the limitation of educators who understand local culture, and the influence of modernization that causes a shift in values in the younger generation.